Lower Cretaceous ammonites from the Neuquén Basin, Argentina: The Hauterivian genus Holcoptychites - Aguirre-Urreta, Maria Beatriz (2003)
Holcoptychites is known only from the Neuquén Basin, Argentina, but appears close to the more widespread genera Jeanthieuloyites and Spitidiscus. Thus it is placed in the subfamily Spitidiscinae (Family Holcodiscidae). Previously described Holcoptychites species are revised and their taxonomy clarified, while one new species is left under open nomenclature. The sequence of forms allows two subzones to be recognized. These are correlated provisionally with the lowest Hauterivian Acanthodiscus radiatus Zone of the Mediterranean region.